Cancer Prevention with Molecular Target Therapies 4.0 (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Personalized medicine is playing an important role in cancer prevention. To date, it is clear that many cancers are molecularly distinct subtypes, and different therapeutic approaches are required for each. Indeed, the identification of cancer susceptibility genes permits identifying patients “at risk” of developing neoplasia and supports modifying individual risk behaviors or the choice of preventive therapy. Additionally, the efficacy of various targeted therapies in different cancer subtypes suggests that treatment choices in the near future will be increasingly centered on molecular signatures. Data from preclinical, clinical and observational studies have revealed the ability to prevent cancer development for compounds with different indications than cancer. The concept of drug repurposing permits combinations that can target several critical pathways of a specific disease, decreasing the risk of resistance observed when using single-agent targeted therapy. This open access Special Issue collates original research and review articles on molecular oncology, with an emphasis on the early detection and prevention of cancer. It highlights new findings, methods and technical advances in molecular cancer research.